ANALISIS SISTEM AKUNTANSI SIKLUS PENGGAJIAN DAN PENGUPAHAN KARYAWAN DALAM USAHA UNTUK MENDUKUNG PENGENDALIAN INTERN PERUSAHAAN - Elex Sarmigi (Jurnal Ekonomi Sakti, 2020)
This study aims to determine the analysis of the accounting system in the payroll cycle and employee wages in an effort to support the company's internal control at PT. Perkebunan Nusantara VI Kayu Aro Jambi - Sumbar Business Unit. the company has a weakness in the timekeeper section or Administration section that handles two tasks. This research is a type of field research field research, with a qualitative descriptive method. The data used in this study are primary data and secondary data obtained from the activities of observation, interviews and documentation on one of the employees of PT. Perkebunan Nusantara VI Kayu Aro Jambi - Sumbar Business Unit. The technique of collecting data is done through observation, interviews, and documentation. The results of the study of Accounting System Analysis on the Payroll Cycle and Employee Wages in an Effort to Support the Company's Internal Control (PT. Nusantara Nusantara VI Timber Business Unit Aro Jambi-Sumbar), shows that the payroll and wage system is in accordance with established accounting standards. However, the implementation of internal control is still relatively weak, not yet fully in accordance with the accounting standards applied because the administration part covers the double work.